STATUS PERATURAN DESA DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA (Lex Jurnalica, 2021)
After the enactment of Law No. 12 of 2011, village regulations were not explicitly mentioned in the hierarchy of laws and regulations in Indonesia. Contradictory to this, in Law No. 10 of 2004 village regulations are explicitly stated in the hierarchy of laws and regulations. This research is normative juridical by using a statutory approach.. The results of this paper are from the side of the location of the legislation it can be seen whether a regulation is included in the category of legislation or not. Village regulations prior to the enactment of Law No. 6 of 2014 were promulgated in the Regional Gazette and Regional News, so according to the provisions regarding the location of legislation regulated in Article 81 of Law No. 12 of 2011 the status of village regulations is in the category of legislation. Meanwhile, after the enactment of Law no. 6 of 2014 in accordance with article 69 (1), village regulations are promulgated in the Village Gazette and Village Gazette. This does not meet the provisions of Article 81 of Law No. 12 of 2011 so the status of village regulations is not included in the category of statutory regulations.Keywords : Hierarchy, village regulations, subdelegation